Tamar Bridge, UK: a decade of maintenance from 2010 to 2020. Issue 4 (2nd September 2019) - Baron, Stephen; Urbans, Beverley; Cole, Richard
Abstract : Opened in 1961, Tamar Bridge in Plymouth, UK, is now approaching the mid-point of its original design life and has already undergone a significant modification during the strengthening and widening works of 2001. The 335 m span suspension bridge is owned and operated by the Tamar Bridge and Torpoint Ferry Joint Committee and raises virtually all of its operational and maintenance revenue from traffic tolls. The current decade has included some significant programmes of maintenance with further works planned through to 2020. Specific projects have included resurfacing, comprehensive improvements to access provisions, main-deck expansion joint replacements, truss steelwork recoating and suspension system remedial works. It is hoped that these will secure a continued high level of reliability of service for bridge users over the coming decades while minimising the requirements for raising additional maintenance funding in the form of toll increases.